1991
DOI: 10.1111/j.1365-2494.1991.tb02213.x
|View full text |Cite
|
Sign up to set email alerts
|

Slug density‐seedling establishment relationships in a pasture renovated by direct drilling

Abstract: Ryegrass and white clover were sown singly or in combination at various seeding rates by direct drilling into plots in which a range of slug densities had been established by molluscicide baiting. For both ryegrass and white clover, weights of individual seedlings and numbers and yields of seedlings per metre of drill row were significantly affected by slug density, ryegrass seed rate, clover seed rate and interactions of these factors. Plant losses increased asymptomatically with slug density, indicating high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
4
2
Order By: Relevance
“…Our results do not support the general importance ascribed to gastropod fecundity for their impacts (Barker, ; De Kock & Wolmarans, ; Keller et al., ; Rumi et al., ). Rumi et al.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Our results do not support the general importance ascribed to gastropod fecundity for their impacts (Barker, ; De Kock & Wolmarans, ; Keller et al., ; Rumi et al., ). Rumi et al.…”
Section: Discussioncontrasting
confidence: 96%
“…Our results do not support the general importance ascribed to gastropod fecundity for their impacts (Barker, 1991;De Kock & Wolmarans, 2008;Keller et al, 2007;Rumi et al, 2010 only reached a score of MN (Table 1). These conflicting results may be due to the context dependency of alien introductions.…”
Section: South Africa May Be Particularly Vulnerable To High Impacts Bycontrasting
confidence: 94%
“…Fenner (39) observed that the vulnerability of seedlings to snail ( Helix aspersa Müller) predation decreased rapidly with time and increase in seedling size; therefore conditions that slow seedling growth are likely to increase snail predation and reduce seedling survival. Legumes appear to be particularly vulnerable to mollusk damage when sown with minimal tillage (74) and are likely to be preferentially grazed in mixed pastures (5). Fungicidal seed dressing can increase establishment and early season yield of resown grasses (60) but there is little evidence of a difference in establishment response to fungicide use between seeds sown into cultivated ground and those sown by minimal tillage.…”
Section: Effects Of Minimal‐tillage Practices On Pasture Plant Emergencementioning
confidence: 99%
“…Lewis (61) suggested that increased soil bulk density might reduce seedling growth rate and prolong the period of greatest risk for pathogen infection, and it could be inferred that reduced tillage would thus increase the risk of disease infection and reduce seedling establishment. The effectiveness of pesticide or fungicide in improving yield is variable, and depends on the extent of pest or disease challenge to the crop (5,54,97). Modification of planting dates to avoid periods of high pest population may be more effective than pesticide application in reducing the effects of predators (15,54,74).…”
Section: Effects Of Minimal‐tillage Practices On Pasture Plant Emergencementioning
confidence: 99%
See 1 more Smart Citation